1999
DOI: 10.1136/vr.144.13.343
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and hormonal responses of cows to treatment with an analogue of gonadotrophin releasing hormone and prostaglandin F

Abstract: Blood samples were taken from 11 cows and their ovaries were scanned by ultrasound at least daily. Around day 5 of an induced cycle, they were injected with 10 micrograms buserelin, an analogue of gonadotrophin releasing hormone, and on day 12 they received 0.5 mg cloprostenol, an analogue of prostaglandin F2 alpha (PGF2 alpha). Two days later six of the cows (the treated group) received a second injection of 10 micrograms buserelin, but the remaining five received no further treatment (control group). The dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…The results of this investigation are in agreement with Paul and Prakash (2005), Chenault et al (1990), Peters et al (1999), Sarkar and Prakash (2005), for only ovsynch treatment and with Schallenberger et al (1978) who also observed that inhibition of prolactin secretion with bromocriptine did not affect LH concentration in Brown Swiss cows. Other researchers also reported that administration of bromocriptine in postpartum beef heifers reduced circulatory concentrations of prolactin without having any significant effect on LH, progesterone, estradiol and ovarian activity (Williams 1979;Williams and Ray 1980).…”
Section: Discussionsupporting
confidence: 94%
“…The results of this investigation are in agreement with Paul and Prakash (2005), Chenault et al (1990), Peters et al (1999), Sarkar and Prakash (2005), for only ovsynch treatment and with Schallenberger et al (1978) who also observed that inhibition of prolactin secretion with bromocriptine did not affect LH concentration in Brown Swiss cows. Other researchers also reported that administration of bromocriptine in postpartum beef heifers reduced circulatory concentrations of prolactin without having any significant effect on LH, progesterone, estradiol and ovarian activity (Williams 1979;Williams and Ray 1980).…”
Section: Discussionsupporting
confidence: 94%
“…The circulatory levels of plasma progesterone were basal (≤0.2 ng/ml) at the time of second GnRH injection in all the treated yaks, and continued to stay low up to 24 h. A similar decline in plasma progesterone concentration to basal levels (< 0.1 ng/ml) within 24 h after the PGF 2α administration was observed in Ovsynch‐treated cows (Peters et al. 1999), in Murrah buffaloes (Paul and Prakash 2005) and in yaks (Sarkar and Prakash 2005a,b).…”
Section: Discussionsupporting
confidence: 55%
“…The overall range of diameters of DFs on day 7 (13.4 ± 1.1–15.7 ± 0.6 mm) was slightly greater than the 12.2 mm previously reported by Peters et al at 7 days after giving GnRH alone to cyclic cows. The size and maturity of the DF on day 7 (i.e.…”
Section: Discussioncontrasting
confidence: 59%